Isolation, in vitro study, and stem cell markers for type A spermatogonia in a Characiformes species - Dias, Gisele C. M.; Batlouni, Sérgio R. [UNESP]; Cassel, Mônica; Chehade, Chayrra; De Jesus, Lázaro W. O.; Branco, Giovana S.; Camargo, Marília P.; Borella, Maria I. (Wiley, 2020)
The objective of this study was to establish a protocol for the characterization, isolation, and culture of type A spermatogonia using specific molecular markers for these cells in fish. To this end, adult Prochilodus lineatus testes were collected and digested enzymatically and the resulting testicular suspension was separated using a discontinuous Percoll gradient, followed by differential plating. The cell cultures obtained were monitored for 15 days and analyzed using the immunofluorescence method with anti-Vasa, anti-GFRα1, and anti-OCT4 antibodies. Spermatogonial enrichment was also performed using flow cytometry. Although discontinuous Percoll gradient centrifugation followed by differential plating enabled the removal of differentiated germ cells and somatic cells, enriching the pool of type A spermatogonia, the enrichment of type A spermatogonia through flow cytometry of samples without Percoll proved to be more efficient. Prominent cell agglomerates that were characterized according to different stem cell markers as type A spermatogonia were observed during the 15 days of the cell culture. The use of immunoperoxidase and western blot analysis methods confirmed the specificity of the markers for type A spermatogonia of P. lineatus. When combined with specific cell culture conditions, the positive characterization of these molecular markers clarified certain aspects of spermatogonial regulation, such as survival and proliferation. Finally, understanding the regulation of the in vitro germ cell maintenance process may contribute to the enhancement of in vivo and in vitro reproduction techniques of endangered or aquaculture fish species.
Keywords: cell sorting; differential plating; germ cells; immunocytochemistry; Teleostei